(untitled) (World Bulletin of Management and Law, 2025)
The integration of theory and practice is essential in educational settings, particularly in practical training programs. This article explores the importance of fostering a balance between theoretical concepts and practical application during practical training. We explore how technology can be used to bridge the gap between theory and practice, thereby enhancing the effectiveness of practical training programs. By combining technological tools and innovative approaches, educators can create immersive and interactive learning experiences that foster a deeper understanding of theoretical concepts and their real-world applications. This article provides insight into the advantages, challenges, and best practices associated with using technology to ensure a balance between theory and practice in practical training.